Metode Examples Non Examples Dalam Meningkatkan Prestasi Belajar Siswa pada Mata Pelajaran PAI Kelas VII SMPIT Al-Fikri Depok - Eva Siti Faridah; Yunita Sari; Ernawati Ernawati (Jurnal Dirosah Islamiyah, 2021)
Results of preliminary observations at SMPIF Al-Fikri Depok shows that KKM – Kriteria Ketuntasan Minimum (Minimum Mastery Criterion/students' learning achievement) 72 in Islamic Education subject was low because of the students’ embarrassment to ask questions, not paying attention to lessons and the lack of learning methods used by teachers. One of the factors causing it was that the learning methods used by teachers were less varied so that learning activities were monotonous. The purpose of this research is to find out the effect of applying the Examples Non Examples method in learning PAI. The method used is classroom action research (PTK). The object in this study were 42 students of grade VII. Data was collected by distributing learning achievement questionnaires to each student, and filling out observation sheets. The data was analyzed using quantitative calculations which later translated into presentations. Based on the results of students’ achievements after learning using the Examples Non Examples method, student achievement increases each cycle. The results of the questionnaires in the first cycle was 72.32% and in the second cycle was 83.68%, thus it can be concluded that the application of the Examples Non Examples method has increased students’ learning achievement by 11.11%.